2015
DOI: 10.1007/s11071-015-2236-5
|View full text |Cite
|
Sign up to set email alerts
|

A new car-following model considering driver’s individual anticipation behavior

Abstract: In this paper, a new car-following model of traffic flow is proposed by considering the driver's individual anticipation behavior (forecast behavior and response delay behavior). The effect of anticipation parameters corresponding to the individual differences upon the stability of traffic flow is examined through linear stability analysis. The simulation results are in good agreement with the theoretical analysis and confirm that traffic flow can be stabilized efficiently by drivers' forecast effect (positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The proposed analysis complements and must be taken into considerations for all the studies on traffic flow behaviors. In particular, many studies (also based on bifurcation theory, see, e.g., [31][32][33]) consider how the traffic flow is affected depending on different driver's characteristics, without checking the lateral stability of each driven vehicle.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The proposed analysis complements and must be taken into considerations for all the studies on traffic flow behaviors. In particular, many studies (also based on bifurcation theory, see, e.g., [31][32][33]) consider how the traffic flow is affected depending on different driver's characteristics, without checking the lateral stability of each driven vehicle.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Hence, drivers have to stop approaching the crossing points, which may trigger a traffic wave and last until pedestrians cross. As a result, drivers may slow down proactively on approaching a crossing point in anticipation of a pedestrian crossing maneuvers, particularly if there is a pedestrian platoon waiting by the roadside [46,111]. Moreover, it is observed that the waiting time of pedestrians at zebra crossings reduces by increasing the number of pedestrians at crosswalks [94].…”
Section: Pedestrian Group Sizementioning
confidence: 99%
“…It also affects drivers' behaviors on approaching a road segment with no pedestrian facilities. For example, drivers who are familiar with a road segment are likely to drive cautiously in anticipation of pedestrians' unexpected crossing attempt [111], whilst the pedestrian behavior may be surprising for those who are not familiar and can lead to conflict [46].…”
mentioning
confidence: 99%
“…Furthermore, Deng et al [28] defined a new approach of anticipation based on the leader-follower form and modelling the anticipation effect by introducing an anticipation coefficient measuring the level of anticipation under actual driving conditions. Moreover, a new model of traffic flow is proposed by Yi-Rong et al [29]. They considered the effect of anticipation parameters corresponding to the individual differences in the traffic flow stability.…”
Section: Related Workmentioning
confidence: 99%